Epidemiology of carbon monoxide gas poisoning deaths in Ardabil city, 2008-13 - Farzaneh, Esmaeil; Seraji, Farnaz Nasl; Valizadeh, Behzad (International Journal of Research in Medical Sciences, 2017)
Background: Carbon monoxide gas is odorless, colorless and toxic which are the most abundant pollutants in the lower atmosphere. Carbon monoxide poisoning is considered as one of the most common causes of mortality in Iran and Ardabil province. This study aimed to investigate the epidemiology of carbon monoxide gas poisoning died patients during 2008 to 2013. Methods: In this descriptive cross-sectional study, with referral to the Ardabil coroner center and poisoning ward of Imam Khomeini hospital, the statistics related to carbon monoxide poisoning died patients have been extracted and entered into the Checklists then analyzed by statistical methods in SPSS.19. Results: The number of deceased in this study was 35 people with a mean age of 33.66 ± 21.38. Of them, 19 (54.3%) were male and 16 (45.7%) were female. 85.7 percent of the deceased had been poisoned at home which from them 71.4% died before transaction to hospital. The season winter with 48.6% include the most of cases and the most common vehicle of intoxication was water heater with 48.6%. Conclusion: Carbon monoxide gas poisoning is one of the cases that causes to death of people in Ardabil every year and so promoting public awareness about risks due to Carbon monoxide could have a considerable role in the prevention of poisoning.